2020
DOI: 10.1039/c9cc09477f
|View full text |Cite
|
Sign up to set email alerts
|

Halogen substitution regulates the phase transition temperature and band gap of semiconductor compounds

Abstract: Halogen substitution creates a promising platform for designing and optimizing materials with a combination of attractive dielectric and semiconductor properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…The average cis angle of 89.99 matches the ideal value of 90 , while the average trans Cl-Bi-Cl angle is 176.60 . The above-described structural parameters for 1 and 2 are comparable with those found in other chloridobismuthates(III) with organic cations showing the same inorganic substructures (Li et al, 2020;Anyfantis et al, 2020).…”
Section: Structures Of 1 Andsupporting
confidence: 81%
“…The average cis angle of 89.99 matches the ideal value of 90 , while the average trans Cl-Bi-Cl angle is 176.60 . The above-described structural parameters for 1 and 2 are comparable with those found in other chloridobismuthates(III) with organic cations showing the same inorganic substructures (Li et al, 2020;Anyfantis et al, 2020).…”
Section: Structures Of 1 Andsupporting
confidence: 81%
“…3− anions surround by NH 3 CH 2 CH 2 F + cations to form the zero-dimension structure at 272 K, comparing to (EA) 3 BiCl 6 crystallized in the monoclinic space group P2/c. 46 Owing to the independent BiCl 6 3− anions being separated by NH 3 CH 2 CH 2 F + cations and the nearest Bi−Bi distance being 7.53 Å, the intermolecular coupling between anions could be negligible. It can be concluded that anions were mainly connected by cations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The colorless crystals of (FEA) 3 BiCl 6 were obtained by slow evaporation at room temperature. It adopts an orthorhombic space group P 2 1 2 1 2 with BiCl 6 3– anions surround by NH 3 CH 2 CH 2 F + cations to form the zero-dimension structure at 272 K, comparing to (EA) 3 BiCl 6 crystallized in the monoclinic space group P 2/ c . Owing to the independent BiCl 6 3– anions being separated by NH 3 CH 2 CH 2 F + cations and the nearest Bi–Bi distance being 7.53 Å, the intermolecular coupling between anions could be negligible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations